(untitled) (Research, Society and Development, 2020)
Diabetes Mellitus (DM) is part of a group of metabolic diseases, described by a picture of hyperglycemia resulting from decreased insulin secretion. Functional foods are those foods that are consumed in the diet, in addition to nutritional functions, metabolic and physiological effects on the body. The present study is a review of the literature whose objective is to identify studies that point to the relationship with the consumption of functional foods and their reduction in reducing the development and treatment of Diabetes Mellitus. A survey used as an electronic database - US National Library of Medicine / National Institutes of Health (PUBMED / NCBI) and Google Scholar, with articles from the years 2014 to 2019. It was incorporated to this review 34 studies, 21 in Portuguese and 13 in English. It was evidenced that the consumption of functional foods has effects in the treatment and control of type DM 2. Through this study, it was concluded that in addition to a healthy diet, it includes functional foods in the diet that can reduce the risks for type 2 DM and use in the treatment of the disease. Thus, it is necessary to have the professional accompaniment of a nutritionist, regarding the orientation and inclusion of functional foods.